PENGARUH KEPEMIMPINAN KOLABORATIF DAN KNOWLEDGE SHARING TERHADAP PERILAKU KERJA INOVATIF PEGAWAI MELALUI KECERDASAN EMOSIONAL (STUDI KASUS PADA DINAS SOSIAL KOTA SURABAYA) - Imam Mahmudi; Sundjoto Sundjoto; Sri Rahayu (POLITEKNIK LP3I JAKARTA, 2025)
Innovative human resources are an important predictor of an organization's progress. This requires support from leaders who can create a supportive environment. This study examines the influence of collaborative leadership and knowledge sharing on employees' innovative work behavior through the emotional intelligence. This study was conducted on the entire population of the Surabaya Social Services Office, totaling 108 people. Data collection was conducted using a Likert scale and the data was analyzed using the Partial Least Squares (PLS) method. The results indicate that collaborative leadership and knowledge sharing have a significant effect on emotional intelligence and innovative behavior. Furthermore, emotional intelligence was found to be a mediator between collaborative leadership and knowledge sharing on innovative work behavior.